“The Representation of the Khwarazmshah Dynasty in Ibn Khaldun’s “Tarikh Ibn Khaldun” - Sobirova, Maxzuna I. (Indonesian Journal Publisher, 2025)
This study aims to examine the representation of the Khwarazmshah Dynasty in Ibn Khaldun’s Tarikh Ibn Khaldun and analyze how the dynasty’s political, social, and cultural aspects were reflected in his historiographical framework. Using a qualitative historical method combined with content analysis, the study explores Ibn Khaldun’s narrative, his evaluation of leadership, and the rise and decline of the dynasty within the broader Islamic historical tradition. The results show that Ibn Khaldun portrayed the Khwarazmshah Dynasty both as a powerful regional authority and as an example of political fragmentation that eventually contributed to its decline. His cyclical theory of the rise and fall of states is evident in the narrative, highlighting issues such as governance, legitimacy, and military challenges. The analysis also reveals that Ibn Khaldun’s description reflects not only historical facts but also his philosophical approach to history, offering lessons on statecraft and social cohesion. In conclusion, Ibn Khaldun’s representation of the Khwarazmshah Dynasty demonstrates the integration of historical events with theoretical reflections. This study contributes to a deeper understanding of Islamic historiography and provides new perspectives on how medieval Muslim scholars interpreted political dynamics in Central Asia.